An Unusual Case of Tracheoesophageal Fistulae - Jadelis Giquel; Christina Matadial; Yiliam F. Rodriguez Blanco; Ricardo Martinez-Ruiz; Dao Nguyen; Keith Candiotti (Case Reports in Medicine)
Acquired tracheoesophageal fistulae (TEF) are commonly due to malignancy (M. F. Reed and D. J. Mathisen, 2003). We present the case of a patient with a deceptive history for TEF and report an approach that provides adequate oxygenation, ventilation, surgical exposure, and postoperative analgesia with excellent outcome.